REKONFIGURASI STRATEGI PEMASARAN DIGITAL: DARI KONTEN BERBASIS AI MENUJU BRANDING AUTENTIK DALAM ERA KOMUNITAS MIKRO DAN SOCIAL COMMERCE 2.0 - Moh Gufron Romadhoni (CV. Adiba Aisha Amira, 2026)
This study examines the reconfiguration of digital marketing strategies from AI-generated content toward authentic branding in the era of micro-communities and Social Commerce 2.0. The rapid advancement of artificial intelligence has enabled firms to produce content efficiently, personalize communication, and optimize marketing performance. However, the dominance of AI-driven content raises concerns regarding declining authenticity, reduced emotional engagement, and weakening brand trust among consumers. In parallel, the emergence of micro-communities has shifted consumer behavior toward trust-based interactions, where authenticity and shared values play central roles in shaping purchasing decisions and brand perceptions. This research adopts a library research approach by systematically reviewing recent scholarly literature indexed in Scopus (2020–2025). The analysis focuses on three key dimensions: artificial intelligence in marketing, authentic branding, and brand equity within social commerce ecosystems. Through qualitative content analysis, this study synthesizes theoretical perspectives and empirical findings to develop an integrated conceptual understanding of the evolving digital marketing landscape. The findings reveal that while AI enhances efficiency and scalability, it cannot fully substitute for authenticity in building long-term brand equity. Authentic branding—characterized by transparency, consistency, and emotional resonance—emerges as a critical determinant of consumer trust and engagement. Furthermore, micro-communities serve as influential platforms that amplify authentic brand narratives and reinforce consumer loyalty. The study highlights the need for a balanced strategy that positions AI as an enabler while maintaining a human-centered approach to marketing. This research contributes to the literature by bridging the gap between technology-driven and human-centric marketing paradigms. It offers practical implications for businesses to integrate AI capabilities with authentic brand values in order to remain competitive and relevant in the evolving digital ecosystem.